Kebebasan berpendapat di media sosial: Antara hak dan batasan - Lestari, Rizka Dwi; LESTARI, RIZKA DWI (Maliki Interdisciplinary Journal, 2026)
The Law on Information and Electronic Transactions (ITE Law) has generated public concern because criticisms and opinions expressed in digital spaces are often monitored and may even lead to legal action due to alleged violations of the law. This study is intended to examine the legal position of the right to freedom of expression on social media platforms, including the limitations and regulations governing its implementation. By applying a normative legal research method, the study analyzes the substance of freedom of expression as guaranteed in the 1945 Constitution of the Republic of Indonesia and the Universal Declaration of Human Rights (UDHR). The discussion is further developed through conceptual perspectives proposed by legal scholars. The rapid growth of social media platforms as digital spaces has created broader opportunities for individuals to convey opinions and distribute information openly. Although the right to express opinions in the digital sphere is legally recognized, its exercise must remain in accordance with existing legal provisions. Therefore, this research concentrates on explaining and analyzing the regulatory framework governing freedom of expression and self-expression on social media in Indonesia, while also evaluating whether these regulations align with the principles of human rights protection.